QUIZIZZ APPLICATION AS A MEDIUM FOR EVALUATING TARJAMAH LEARNING - Fitri, Natasya Ayu; Ilham, Muhammad; Susanti, Triana (Proceeding of International Conference of Islamic Education, 2024)
This research aims to analyze the use of the Quizizz application as a medium for evaluating tarjamah learning. This research was motivated by the difficulty of teachers correcting students' answers and requiring more time to add more questions. This type of research is descriptive qualitative. Data collection using observation and interview instruments. The results of this research are: Based on the results of the research that has been carried out, it can be concluded that teachers can save time in creating questions without printing question sheets and adding more questions, making it easier for teachers to correct student answers, as well as making the tarjamah learning evaluation process faster with the Quizizz Application. The use of Quizizz also has a positive impact on the learning process, including increasing student interaction, motivation, and the effectiveness of learning evaluation. Quizizz can also be used as a cooperative learning tool, where students can work together in answering questions and compete for points. Thus, this journal concludes that the use of the Quizizz application as a medium for evaluating Arabic tarjamah learning has great potential to improve student learning outcomes through an interactive, fun and technology-based approach.